Development of an IoT-enabled Smart Library System for a University Campus - Gupta Sungkur, Yash; M. S. Ozeer, Azhar; D. Nagowah, Soulakshmee (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2021)
With the accelerated advancement in technology infrastructure, the concept of libraries in the educational institution has evolved from a traditional system, which consists of several manual processes requiring human intervention to perform critical tasks, to that of a smart library system where the core activities are automated through the use of Internet of Things (IoT) devices. Integrating IoT devices in the different processes enables the streamlining of such processes rendering them more efficient through the capture of real-time data as they are being generated. This paper describes the implementation of a smart library system in a university campus using IoT devices. The system makes use of analytics and machine learning to analyze trends and make predictions. The system prototype is presented in the paper.